1988
DOI: 10.1159/000181000
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic-Pituitary-Testicular Axis in Patients with Hyperthyroidism

Abstract: To test whether chronic thyroid hormone excess influences the hypothalamic-pituitary-testicular axis, 8 hyperthyroid men were given two identical intravenous GnRH tests. The first test was performed before any treatment had been instituted, the second 6–13 months later, when medical treatment had made the patients euthyroid. Although basal serum luteinizing hormone (LH), follicle-stimulating hormone (FSH) and testosterone (T) levels were of similar magnitudes before and after the medical treatment, LH and FSH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 18 publications
1
13
0
3
Order By: Relevance
“…However, the plasma level of free testosterone is not significantly different from normal (21,22), whereas bioavailable testosterone has been reported recently to be low (19). Basal levels of gonadotropins are usually normal, with LH and FSH responses to exogenous GnRH significantly greater than those of controls (25). Serum progesterone levels are also elevated in these patients (22).…”
Section: Discussionmentioning
confidence: 85%
“…However, the plasma level of free testosterone is not significantly different from normal (21,22), whereas bioavailable testosterone has been reported recently to be low (19). Basal levels of gonadotropins are usually normal, with LH and FSH responses to exogenous GnRH significantly greater than those of controls (25). Serum progesterone levels are also elevated in these patients (22).…”
Section: Discussionmentioning
confidence: 85%
“…LH and FSH response to exogenous GnRH seems to be significantly greater in thyrotoxic patients in comparison to patients who were rendered euthyroid (44,45). It has been suggested that the LH elevation could be secondary to changes in sex steroid binding and peripheral metabolism, alterations in the hypothalamic-pituitary feedback, or due to the direct effect of thyroid hormones per se at this level (45). All these changes are fully reversible with restoration of the euthyroid state, and require no other specific treatment.…”
Section: Thyroid Hormone Disorders and Androgenic Hormonesmentioning
confidence: 99%
“…Several studies have shown that altered thyroid status has remarkable effects on Leydig cell differentiation in experimental animals dism, pituitary hyperplasia may occur causing multiple pituitary hormone deficiencies, including gonadotropin and corticotropin deficiencies (45). Low T3, high TSH and hyperprolactinemia caused by hypothyroidism could directly act on the Leydig cells in suppressing steroidogenesis (42,43,46).…”
Section: Thyroid Hormone and Testicular Functionmentioning
confidence: 99%
“…The neuropsychiatric effects of thyroid dysfunction may independently contribute to sexual dysfunction in men with untreated thyroid disease; however, several biochemical relationships have also been observed. There is an increased gonadotroph response to GnRH in men with untreated hyperthyroidism compared to when treatment had rendered the men euthyroid, suggesting a possible role of thyroid hormone in sensitization of gonadotrophs (61). Hypothyroidism has been associated with low total testosterone levels, assumed to be due to low SHBG levels (13,62).…”
Section: Thyroid Issuesmentioning
confidence: 99%